1980
DOI: 10.1002/path.1711310208
|View full text |Cite
|
Sign up to set email alerts
|

Induction of macrophage DNA synthesis In vitro, by non‐immunological inflammatory sera: Effect of irradiation and thymus or bone marrow cell reconstitution

Abstract: The mitogenic activity on macrophages of acute inflammatory serum is increased when this serum is obtained from irradiated rats. Transfer to irradiated rats of normal syngeneic thymic or bone marrow cells enhances the mitogenic activity of inflammatory serum. The enhancement of mitogenic activity is more pronounced after transfer of cells harvested from rats with an acute inflammatory reaction. It is postulated that the mitogenic activity of inflammatory serum could be related to both thymic and bone marrow ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, since our fraction has a molecular weight between 50(02000 it may be assumed that it is not either a monokine or lymphokine. The existence of a mitogenic factor for macrophages has been demonstrated in the serum of rats having undergone an acute nonspecific inflammatory reaction [15] which has similar molecular weight characteristics to the factor described here [16]. This factor is thought to be of~a peptidic nature since the mitogenic activity for macrophages can be destroyed by prior incubation with trypsin or pronase (unpublished observations).…”
Section: Influence Of Fractionated Inflammatory Serum On 100 the CL Rmentioning
confidence: 57%
“…However, since our fraction has a molecular weight between 50(02000 it may be assumed that it is not either a monokine or lymphokine. The existence of a mitogenic factor for macrophages has been demonstrated in the serum of rats having undergone an acute nonspecific inflammatory reaction [15] which has similar molecular weight characteristics to the factor described here [16]. This factor is thought to be of~a peptidic nature since the mitogenic activity for macrophages can be destroyed by prior incubation with trypsin or pronase (unpublished observations).…”
Section: Influence Of Fractionated Inflammatory Serum On 100 the CL Rmentioning
confidence: 57%
“…Additional studies using inflammatory exudate from calcium pyrophosphate injected rats demonstrated that the exudate, when cultured with spleen cells, was able to modulate their response to the mitogen phytohaemagglutinin (PHA) [3]. It was suggested that the mitogenie activity of inflammatory serum could be related to both thymic and bone marrow cells and that this cellular activity is enhanced when inflammation is present [5]. For example, sera obtained from such animals reduced the chemotactic responsiveness of polymorphonuclear leukocytes [4].…”
Section: Introductionmentioning
confidence: 99%